Pengaruh Faktor-Faktor Ekonomi Makro Terhadap Stabilitas Perbankan Di Indonesia - Frido Evindey Manihuruk; Arsiska Sari; Gresia Septina Sitohang; Hasyim Hasyim (Akuntansi, 2024)
Banking stability has become an important issue in the economy, especially after the 1998 Asian economic crisis and the 2008 global crisis which showed that the economic stability of a country is strongly influenced by the stability of its financial system. This study aims to analyze the influence of macroeconomic factors such as inflation, interest rate (BI Rate), and rupiah exchange rate on banking stability in Indonesia. Using a quantitative approach and multiple regression analysis, it was found that interest rates (BI Rate) and the rupiah exchange rate have a significant influence on banking stability, while inflation was not found to have a significant influence. Interest rates affect stability through the cost of funds incurred by banks, while a stable rupiah exchange rate increases investor confidence and lowers exchange rate risk, strengthening financial system stability. The non-significant effect of inflation may be due to the banking sector's ability to adjust interest rates and effective risk management strategies. The results emphasize the importance of effective monetary policy and exchange rate risk management to maintain banking stability in Indonesia. This research provides valuable insights for regulators in formulating policies that support banking stability and sustainable economic growth.